Disaster preparedness and management mechanisms in Zimbabwe: a critical analysis of the Tokwe-Mukosi floods in Masvingo Province. - Moyo, Shelton (2017)
This study examined Zimbabwe’s disaster preparedness and management mechanisms. It used the Tokwe Mukosi floods as a case study. The study employed both qualitative and quantitative approaches. The study had discussions with key stakeholders at provincial, district and community level as well as randomly sampled households. Quantitative Household Questionnaires and Qualitative Key Informant Interviews were used to collect the data. The study established that Zimbabwe’s disaster management strategies are very poor for the government on its own cannot curb these disasters. These recommendations have been proposed: -The government should have a policy framework to cope up with disasters. -Disaster risk management should be integrated in development planning and management at whatever level of governance in Zimbabwe and even at schools. -The civil protection unit should conduct trainings at national, provincial, district and community level on disaster risk reduction. Communities themselves should not only blame the government but also try their best to protect themselves from disasters. -The government should have an operational budget to facilitate quick responses when disasters occur. Currently the government has no standing budget for disaster risks. This has caused the government to fail to curb disasters in time as it will need to first seek support from the international community and nongovernmental organisations when disasters happen. -The government has failed to fully compensate the flood victims. Therefore the researcher recommends the government to formulate a broader framework for restoring livelihoods and compensating the victims who will have lost many valuables from the disaster. - According to experts there is now 90% probability for high rainfall because of climate change. Therefore the government should facilitate evacuations before climate induced disasters occur. People should be removed from river basins to areas which are not flood prone. -The responsible authorities especially the metrological services department should conduct awareness campaigns on impending seasonal hazards. -The impact of disasters is now known to be devastating basing on the Tokwe Mukosi disaster. Therefore there should be the establishment of civil protection committees at community level to national level with clear terms of reference to improve the response rate, when disasters strike. - Reliance on early warning systems is also another recommendation. It is alleged that the Tokwe Mukosi disaster has been detected by meteorologist but no action was taken. This may be because weather forecasts especially in Zimbabwe are not reliable. People should rely on weather forecasts. -The government should invest in technical capacity for quick and accurate assessments of disaster situations and a rapid mechanism to active support from the international community because it is standard practise that international aid agencies will not offer support unless government calls . - Furthermore the government should not abuse NGOs operating in their country. This can lead to withdrawal of aid as witnessed by UNICEF and OXFAM. -The government should be found on the forefront when disasters occur and what people witnessed at Tokwe- Mukosi where NGOs were found highly active than the government itself. NGOs should play a second fiddle.